Territorial Changes of the Rzeszów Region — Rzeszowskie Voivodship in the Years 1944–1998 - Zbigniew Kalandyk (Barometr Regionalny)
The article presents the territorial changes of the Rzeszowskie Voivodship in the years 1944–1998, which were frequent in this period. Initially, the reason was uncertainty about the final shape of the eastern Polish border, later changes occurred as a result of exchange of sections of borderland territories with the USSR, correction of borders with neighboring provinces and finally reforms of the administrative divisions of the state of 1975 and 1998.